Aktivitas Antioksidan Ekstrak Fenol Daun Gayam (Inocarpus fagiferus Fosb) - Dwi Marga Lestari; Nurul Mahmudati; Sukarsono Sukarsono; Nurwidodo Nurwidodo; Husamah Husamah (Fakultas Biologi | Universitas Jenderal Soedirman, 2018)
This study aims to determine the total phenolic content and antioxidant activity in gayam leaf extract (Incarpus fagiferus Fobs). The research method used is a quasi-experiment that aims to predict the situation to be achieved through actual experiments but no treatment. The sample used is old gayam leaves, with the characteristic of dark green leaf and rough leaf surface. The process of preparing simplicia, ie preparing fresh gayam leaves, dried in an oven temperature 45-50oC, and then dried to produce gayam leaf powder. Samples were extracted with methanol solvent and ethanol for 5 days. The total phenol assay method uses Folin-Ciocalteau method and antioxidant activity test using DPPH free radical retardation method (1,1-diphenyl-2-picrylhydrazyl). The results showed that the total phenolic content of gayam leaf extract with ethanol and methanol solvent was 313,704 GAE (Gallic Acid Equivalent) and 273,913 GAE, respectively. Antioxidant activity as a free antidote to free radical DPPH is known to be valued with IC50 (inhibitory concentration).